2011
DOI: 10.3109/01612840.2011.598606
|View full text |Cite
|
Sign up to set email alerts
|

“Left Alone with Straining but Inescapable Responsibilities:” Relatives’ Experiences with Mental Health Services

Abstract: Relatives of persons with severe mental illness experience burden and straining changes in their lives that put their health at risk. Consequently, they need support from health professionals. The aim of this study was to describe experiences from encounters with mental health services as seen from the point of view of relatives of persons with severe mental illness. A qualitative, explorative study was performed, based on two open-ended questions in a cross-sectional study of relatives' health, burden, and se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
50
2
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 29 publications
3
50
2
3
Order By: Relevance
“…Although searching for hope, our findings show that relatives’ hope could diminish as they experienced a lack of recovery or of follow‐up from mental health care services, further complicated by having to balance the personnel’s boundaries for acceptable ‘interfering’ from relatives (40). To experience relief from one’s own burden may build hope in relatives (38), and carer burden can be reduced if the patient’s needs are met by the health services (41).…”
Section: Discussionmentioning
confidence: 92%
“…Although searching for hope, our findings show that relatives’ hope could diminish as they experienced a lack of recovery or of follow‐up from mental health care services, further complicated by having to balance the personnel’s boundaries for acceptable ‘interfering’ from relatives (40). To experience relief from one’s own burden may build hope in relatives (38), and carer burden can be reduced if the patient’s needs are met by the health services (41).…”
Section: Discussionmentioning
confidence: 92%
“…If relatives are to be a treatment resource, clinicians must provide for a strengthening of their role (Kaplan, Turner, Norman, & Stillson, 1996). As Weimand, Hedelin, Hall-Lord, and Sällström (2011) showed, relatives of people with severe mental disorders need support to master their role as relatives. They need to feel that their experience is acknowledged and worked on.…”
Section: Discussionmentioning
confidence: 99%
“…A closer and more inclusive collaboration with health professionals was found to be important, which corresponds with Perreault et al [5] and Schröder et al, [28] who found collaboration to be a key element and predictor of relatives' satisfaction with the mental health services. According to Rowe [36] and Weimand et al, [37] collaboration should be characterized by a more empathic communication in which mental health-care personnel encounter relatives with openness and interest. In Kim's [38] typology of theoretical domains for nursing, the three phenomena of contact, communication and interaction are highlighted in the Client-Nurse domain.…”
Section: Discussionmentioning
confidence: 99%